UNDERSTANDING CORRUPTION IN EDUCATION IN A NEOLIBERAL WORLD: THE CASE OF THE PHILIPPINES - Rohaiba B Radiamoda (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2018)
Corruption is deeply rooted in the education sector of the Philippines. It poses a challenge that requires deeper analysis and understanding into its roots and dynamics. The substantial infiltration of neoliberalism into the educational system of the country has opened it wide to legitimate and systematize foreign control propagating US and other foreign economic interest while maximizing the efficiency of exploitation of the Philippine natural resources and skilled laborers. Given the massive gap of wealth and income between the rich and poor in a resource-depleted country like the Philippines, which has mainly been due to the neoliberal economic policies of the country, this paper argues that using some key ideas of the political philosopher Karl Marx, one can understand fully well the roots of the corruption, most especially on education, in the country. It was found out that endemic corruption within Philippine education sector is traceable to the structural inequalities prevalent in the societal milieu of its semi-feudal, semi-colonial status and continues as the world progresses where countries, like the Philippines, are reorganized to join the trends of neoliberalism. Hence, any meaningful intervention or genuine change, be it educational, institutional or societal, must be directed towards greater understanding of the historical roots and societal dynamics that played its role in entrenching corruption in the nation and furthering the alienated, oppressed and dehumanized conditions of the people.Keywords: corruption, neoliberalism, Philippines, education, Marxism